Antidepressive-like Behavior-Related Metabolomic Signatures of Sigma-1 Receptor Knockout Mice - Svalbe, Baiba; Zvejniece, Baiba; Stelfa, Gundega; Vilks, Karlis; Vavers, Edijs; Vela, José Miguel; Dombrova, Maija; Zvejniece, Liga (MDPI, 2022)
Sigma-1 receptor (Sig1R) has been proposed as a therapeutic target for neurological, neu-rodegenerative, and psychiatric disorders, including depression and anxiety. Identifying metabolites that are affected by Sig1R absence and cross-referencing them with specific mood-related behaviors would be helpful for the development of new therapies for Sig1R-associated disorders. Here, we examined metabolic profiles in the blood and brains of male CD-1 background Sig1R knockout (KO) mice in adulthood and old age and correlated them with the assessment of depression-and anxiety-related behaviors. The most pronounced changes in the metabolic profile were observed in the plasma of adult Sig1R KO mice. In adult mice, the absence of Sig1R significantly influenced the amino acid, sphingolipid (sphingomyelin and ceramide (18:1)), and serotonin metabolic pathways. There were higher serotonin levels in plasma and brain tissue and higher histamine levels in the plasma of Sig1R KO mice than in their age-matched wild-type counterparts. This increase correlated with the reduced behavioral despair in the tail suspension test and lack of anhedonia in the sucrose preference test. Overall, these results suggest that Sig1R regulates behavior by altering serotonergic and histaminergic systems and the sphingolipid metabolic pathway. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: Research Subject Categories::PHARMACY::Biopharmacy